Pengembangan Bisnis Ala Suku Quraisy: Kajian Tafsir Surat al-Quraisy - Fairuzabadi, Mochammad (Adh Dhiya | Journal of The Quran and Tafseer Studies, 2024)
This study explores the business development contained in Surat Quraisy. Using the tafsir bi ar-ra’yi method, this study investigates the verses of the Qur'an with sexual and contextual analysis and logic. It was found that Surat Quraisy provides lessons on perseverance, market segmentation, and balance between business and worship. Through a literature study, this study compares its results with previous studies that also examined this, identifying several implied business strategies, such as perseverance, market segmentation, and balance between business and worship. Previous studies highlight the values ​​that can be taken from the letter, including planning, market understanding, and managerial. The results of the analysis show that Surat Quraisy teaches the importance of perseverance in business, a careful understanding of the market, and a balance between worldly and afterlife affairs. This study reveals the wisdom contained in religious texts and their relevance to contemporary business practices. Thus, this study provides a deeper understanding of the business strategies contained in Surat Quraisy and their implications in current business practices.